Hubungan Fleksibilitas Otot Hamstring Dengan Nyeri Punggung Bawah Pada Pasien Poli Fisioterapi Di Rumah Sakt Petrokimia Gresik - Heppy Romadhani Yudhaningrum; Angria Pradita; Agung Hadi Endaryanto; Fransisca Xaveria Hargiani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
ABSTRACTHeppy Romdhani Yudhaningrumi, 2022, The Relationship Of Hamstring Muscle Flexibility With Lower Back Pain Patients In Poly Physiotherapy Petrokimia Gresik Hospital, Angria Pradita (Pembimbing I), Agung Hadi E (Pembimbing II)Â Low back pain which is one of the musculoskeletal disorders is an accumulation of pain in the context of work and clinically may be caused by work or can be exacerbated by work activities. This condition hampers people's ability to perform various types of work inside or outside the home and interferes with mobility. The risk of low back pain is related to the lack of hamstring flexibility which causes susceptibility to musculoskeletal injury. This study aims to identify the relationship between hamstring muscle flexibility and low back pain.This study has 40 respondents. The design of this study uses a type of correlation with a cross sectional approach. Bivariate analysis in this study used Kendall's Tau.The results of this study are that most of the flexibility of the hamstring muscle is below the average of 62.5%, most of the respondents' low back pain is mild pain of 62.5%, and there is a relationship between hamstring muscle flexibility and low back pain in Physiotherapy Poly at the Petrokimia Gresik Hospital with p-value = 0.000 (p<0.05).This research is expected to be input for additional information based on data and theory to improve the quality of physiotherapy services by educating the public about how to maintain hamstring muscle flexibility and handling low back pain correctly.Â Keyword: hamstring muscle flexibility, low back pain, physiotherapy